Analisis Kinerja Keuangan dengan Menggunakan Metode Rasio Return On Aset (ROA) dan Return On Equity (ROE) pada PT. Royal Prima Tbk - Syahputri, Lailan; Suprayitno, Eddi; Syafrizal, Syafrizal (Universitas Islam Islam Sumatera Utara, 2023)
This research aims to determine the financial performance of PT. Royal Prima Tbk for the 2019-2022 period using the Return On Aset and Return On Equity ratios and to provide evidence that the Return On Assets and Return On Equity methods are effectively use in assessing financial performance at PT. Royal Prima Tbk for the 2019-2022 period. The type of research used is quantitative descriptive analysis, namely by collecting,clarifying, analyzing and interpreting data obtained from the company so that it can provide a picture of the actual situation. Result from financial performance research ata PT. Royal Prima Tbk for the 2019-2022 period is said to be not good, because the average value of Return On Asset and Return On Equity is less than the industri average standard. Therefore, PT. Royal Prima Tbk must be able to improve its financial performance optimally and optimally